The solar-assisted heat pump systems for space and water heating - Aşçıoğlu, İffet Naz. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
In this study, solar-assisted heat pump systems, their contribution to reduce the consumption of non-renewable energy and their compensation for some of the shortcomings of the individual systems are considered. The base solar systems and base heat pump systems are also covered, before going into the hybrid systems. Three special types of solar-assisted heat pump systems such as parallel, series and dual systems are included,and closely examined in various aspects. Their advantages over the base solar energy systems and the base heat pump systems and also over one another are stated. The efficiency of each system and the ways to improve the efficiency is discussed.
Keywords: Heat pumps.; Solar heating.; Solar space heating.; Solar water heaters.